In vitro killing assays of antisera antibody sheep post-infected with Fasciola gigantica with the presence of macrophages cells against homologous and heterologous liver flukes - S.E Estuningsih; S Widjajanti; S Partoutomo; T.W Spithill (Indonesian Center for Animal Research and Development (ICARD), 1999)
The previous artificial infection known that the Indonesian Thin Tail (ITT) sheep was resistance against the liver fluke of Fasciola gigantica, the resistances occurred in the early infection. In order to observe the immune resistance, some in vitro studies were undertaken in the laboratory, to assay the ability of the antisera antibody of ITT sheep post-infected with F. gigantica, with the presence of macrophages cells in killing the homologous and heterologous liver flukes. The viability of liver flukes were observed within 24-72 hours of incubation period by observing their motility (motile flukes were designated live and non-motile once were death). The results showed that after 72 hours incubation, the motilities of the Newly Excysted Juvenile (NEJ) of F. gigantica incubated with the presence of post-infected sera and macrophages cells solution were significantly lower (P<0.05) than that of normal sheep sera. On the contrary, the post-infected sera and macrophages cells solution did not reduce the motilities of the NEJ of F. hepatica, and the death of these flukes were not significantly reduced (P >0.05). It seems that the occurrence of homologous antibody to the antigens is very important in the development of killing mechanism. The absence of homologous antibody did not reduce the number of flukes or the ability of macrophages cells in killing F. hepatica was not apparent. Key words : In vitro studies, ITT sheep, macrophages cells, Fasciola gigantica, Fasciola hepatica